Bridging epigenomics and tumor immunometabolism: molecular mechanisms and therapeutic implications - Xie, Xiaowen; Liu, Weici; Yuan, Zhiyuan; Chen, Hanqing; Mao, Wenjun (Molecular cancer, 2025)
Epigenomic modifications-such as DNA methylation, histone acetylation, and histone methylation-and their implications in tumorigenesis, progression, and treatment have emerged as a pivotal field in cancer research. Tumors undergo metabolic reprogramming to sustain proliferation and metastasis in nutrient-deficient conditions, while suppressing anti-tumor immunity in the tumor microenvironment (TME). Concurrently, immune cells within the immunosuppressive TME undergo metabolic adaptations, leading to alterations in their immune function. The complicated interplay between metabolites and epigenomic modulation has spotlighted the significance of epigenomic regulation in tumor immunometabolism. In this review, characteristics of the epigenomic modification associated with tumors are systematically summarized alongside with their regulatory roles in tumor metabolic reprogramming and immunometabolism. Classical and emerging approaches are delineated to broaden the boundaries of research on the crosstalk research on the crosstalk between tumor immunometabolism and epigenomics. Furthermore, we discuss potential therapeutic strategies that target tumor immunometabolism to modulate epigenomic modifications, highlighting the burgeoning synergy between metabolic therapies and immunotherapy as a promising avenue for cancer treatment.